Designing a Web-Based Thesis Title Submission System Using the Codeigniter 3 Framework - Herman, M (Knowbase : International Journal of Knowledge in Database, 2021)
Thesis is a scientific work made by every student on the basis of conducting a research to complete a bachelor's degree program (S1) guided by the guidance of a lecturer who has the capability of the field of study/final project. There are still many students who are confused during the title submission process. There is no information system provided for the submission of Thesis Title, and There is no information system provided by the Information Technology and Computer Education Study Program to submit the thesis title to the Study Program. The type of research used is Research and Development (Research and Development). In this study, researchers used a system model taken from the life cycle, namely the System Development Life Cycle (SDLC). SDLC is one of the traditional ways to maintain, build and replace an information system. From the product test that the author did, the results obtained were the Validity test was obtained with a number of 0.87 with valid criteria, the Practicality test by the supervisor was obtained a value of 0.91 with very practical criteria and the effectiveness test by students of the Informatics and Computer Engineering Education Study Program obtained a score of 0.89 with criteria Very effective. This study aims to produce a Title Submission systemÂ  Web-Based Thesis which is validated and describes its validity, practicality and effectiveness.